Double jeopardy [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2021)
Stone Barrington launches an investigation in coastal Maine, where he confronts high-connected and well-funded family enemies hiding in plain sight among the region's stately houses and private clubs.